Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fneur.2021.615230
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Long-Term Death After Medullary Infarction: A Multicenter Follow-Up Study

Abstract: Background and Purpose: We investigated the risk factors for death in patients with medullary infarction (MI) during a long-term follow-up.Methods: We retrospectively examined 179 consecutive patients (130 men and 49 women) who had clinical and MRI findings consistent with MI between February 2012 and January 2017 at three university hospitals. Long-term outcomes were assessed by telephonic interview. The clinical and radiological features and risk factors for poor outcomes (modified Rankin scale score ≥ 3, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…This was investigated in a study performed in a stroke unit investigating the association. This reported case had good prognostic signs including age and absence of dysphagia as proved in a multi-center study [20]. Hence, it was important after the development of swallowing symptoms to perform radiological re-evaluation in this case which was consistent with the new symptomatology.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This was investigated in a study performed in a stroke unit investigating the association. This reported case had good prognostic signs including age and absence of dysphagia as proved in a multi-center study [20]. Hence, it was important after the development of swallowing symptoms to perform radiological re-evaluation in this case which was consistent with the new symptomatology.…”
Section: Discussionsupporting
confidence: 59%
“…They found that poor long-term results and all cause mortality were not uncommon in medullary infarction. Age, dysphagia and recurrent strokes were the main predictors for that [20].…”
Section: Introductionmentioning
confidence: 94%
“…In the study mentioned above by Kim K et al, the most common etiologies were LVD (34.5%), vertebral artery dissection (9.2%), and cardioembolic (4.2%) [ 11 ]. A study by Zhang DP et al in 2021 found LVD in 59%, SVD in 10.1%, CE in 4.5%, vertebral artery dissection in 11.2%, and unknown in 12.8% of patients [ 12 ]. A study of 130 patients with lateral medullary infarcts by Kim JS et al in 2003 showed large vessel infarction in 50%, arterial dissection in 15%, small vessel infarction in 13%, and cardiac embolism in 5% [ 13 ].…”
Section: Discussionmentioning
confidence: 99%